Analisis Pengaruh Siklus Menstruasi Terhadap Passing dan Shooting Accuracy Atlet Futsal Wanita: Tinjauan Sistematis - Reza Rizki Fahlevi; Elias Sandy; Ajri Nurli Almuhtadi; M. Arief Setiawan; A. Ine Aprilia Damai; Aprillia Wulan Utari (Jurnal Porkes, 2026)
This systematic review analyzes the influence of the menstrual cycle phase on the determinants of passing and shooting accuracy in female futsal athletes. Following the PRISMA 2020 guidelines, a literature search was conducted in PubMed, Scopus, Google Scholar, SPORTDiscus, and Web of Science for articles published between 2015 and 2026. Of the 847 records identified, 22 articles met the inclusion criteria for a narrative synthesis. The findings consistently showed that the follicular phase was associated with superior fine motor skills, better neuromuscular coordination, improved balance, and lower perceived fatigue compared to the luteal phase. Elevated estrogen levels during the follicular phase facilitate the recruitment of motor units and neural drive, which directly support precision-based technical skills. Conversely, the luteal phase characterized by increased progesterone and impaired thermoregulation is correlated with reduced balance, decreased consistency of muscle activation, and increased motor variability. These hormonal fluctuations have direct implications for technical execution in futsal. However, no study has directly measured futsal-specific passing and shooting accuracy across all phases of the verified menstrual cycle, which represents a critical research gap. This review concludes that monitoring the phases of the menstrual cycle needs to be integrated into the periodization of women’s futsal training to optimize technical performance.